Institutionalizing Local Wisdom: Adaptive Governance of Coastal Farmers in Responding to Climate Change in Rokan Hilir, Indonesia - Rambe, Wahyudi; Safitri, Kinanti Indah; Harahap, Rofiandika Romadona; Nhan, Tran Thien (TEMALI : Jurnal Pembangunan Sosial, 2026)
This study analyzes how local wisdom becomes institutionalized within farmer organizations to strengthen adaptive capacity to climate change in tidal coastal agricultural systems in Rokan Hilir Regency, Indonesia. Drawing on the theoretical perspectives of adaptive governance and social–ecological resilience, the study examines how locally embedded ecological knowledge becomes translated into collectively binding rules that communities can enforce and continuously adjust in agricultural management that depends on hydrological dynamics. The research applies a qualitative approach with a multi-site case study design across five tidal coastal villages. The researcher collected data through in-depth interviews with 22 key informants, field observations, and document analysis to reconstruct cross-village institutional processes. The findings show that adaptation unfolds through recurring institutional stages, including ecological sensing and shared interpretation of tidal and salinity signals, rule formulation through collective negotiation, consolidation of collective obligations, rule enforcement through socially legitimate mechanisms, and adaptive evaluation that enables continuous adjustment. The study conceptualizes this process as the Institutionalizing Local Wisdom for Adaptive Management model, which explains how environmental knowledge transforms into coordinated and adaptive collective action. Comparative findings also reveal variations in the level of institutional consolidation across villages in organizing agricultural adaptation practices. The study confirms that strengthening local institutions plays a crucial role in enhancing the adaptive capacity of smallholder farming communities in coastal regions that face high vulnerability to climate change.